A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil - Shimabukuro, Erika Mayumi; Dantas, Galileu P. S.; Lamas, Carlos José Einicker (Zootaxa, 2021)
A new species of Nilotanypus Kieffer is described and illustrated based on male, pupa and larva. Nilotanypus yanomami sp. n. was collected at madicolous system in a mountainous region of northern Amazonia. Additionally, the identification key for males is updated and a distribution map for the Neotropical species is provided.